THE ANALYSIS OF SWEAR WORDS USED BY THE CHARACTERS IN MOONLIGHT - Prayuda, Putu Edy; Suarnajaya, I Wayan; Juniarta, Putu Adi Krisna (Universitas Pendidikan Ganesha, 2019)
This study aimed to find out types of swear words that are used in the moonlight movie and to analyze purposes of the characters. The subject of this research is the characters in Moonlight movie. This research used descriptive qualitative design. This study used Wardhaugh (2006) theory and Andersson and Trudgill (1992) . This research employed two instruments namely the researcher himself and checklist. The result shows that, excretion swear words appeared 38 %, Sex swear words appeared 27 %, religious matter swear word appeared 20 %, mother in law swear words appeared 4 %, animal swear words appeared 7 %, death, and bodily function swear words respectively appeared 2 %. Looking at the purposes of the characters in using swear word the most dominant is used by the characters is auxiliary which appeared 49 % , abusive appeared 47 % , and expletive which appeared 4 %.